2009
DOI: 10.1111/j.1757-1707.2009.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of biofuels from Jatropha curcas in West Africa: a field study

Abstract: In recent years, liquid biofuels for transport have benefited from significant political support due to their potential role in curbing climate change and reducing our dependence on fossil fuels. They may also participate to rural development by providing new markets for agricultural production. However, the growth of energy crops has raised concerns due to their high consumption of conventional fuels, fertilizers and pesticides, their impacts on ecosystems and their competition for arable land with food crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
83
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 19 publications
15
83
3
1
Order By: Relevance
“…Life cycle assessment studies of jatropha claimed that jatropha could be a promising crop for carbon sequestration [27]. Some even stressed the "robust opportunities and the high potential for jatropha to attract carbon credits under the Clean Development Mechanism" [28]. The estimates concerning greenhouse gas reduction from jatropha plantations vary widely in the literature, from 5.5 ton CO 2 /year/ha [29] to 17-25 ton CO 2 /year/ha [30].…”
Section: Jatropha and Cdm Worldwidementioning
confidence: 99%
“…Life cycle assessment studies of jatropha claimed that jatropha could be a promising crop for carbon sequestration [27]. Some even stressed the "robust opportunities and the high potential for jatropha to attract carbon credits under the Clean Development Mechanism" [28]. The estimates concerning greenhouse gas reduction from jatropha plantations vary widely in the literature, from 5.5 ton CO 2 /year/ha [29] to 17-25 ton CO 2 /year/ha [30].…”
Section: Jatropha and Cdm Worldwidementioning
confidence: 99%
“…De las numerosas materias primas presentadas, el Piñón (Jatropha curcas L.) tiene una historia larga y miscelánea. Originalmente aclamada como un "cultivo milagroso" debido a las predicciones de altos rendimientos bajo condiciones marginales de cultivo (4).…”
Section: Introductionunclassified
“…This reduction in GWP is similar to that estimated for other bioenergy crops including oil palm, sunflower, rapeseed, soybean, corn stover, and switchgrass. Achten et al [78] and Ndong et al [74] both concluded that the cultivation step, specifically fertilization, was the largest contributor to observed greenhouse gas emissions. Other factors that contribute to current uncertainty in greenhouse gas emissions and energy yield from biofuels are harvestable yield, rates and magnitude of soil carbon sequestration, irrigation and other management inputs (e.g., pesticides), energy costs associated with raw material acquisition, and co-product allocation.…”
Section: Potential Impact On Climate Changementioning
confidence: 99%
“…A more rigorous analysis of the energetic costs and benefits of biodiesel and ethanol biofuels can be achieved through life cycle assessment, in which energy requirements at all steps in the process are quantified to the extent possible [7]. Using such an approach, several investigations have documented that the production of Jatropha for biodiesel [74] or jet fuel [75] can result in a 55 to 72% savings in greenhouse gas emissions compared with conventional fuel use. Similarly, for Jatropha grown in West Africa and Thailand, the energy yield defined as the ratio of biodiesel energy output compared to the fossil energy input ranged from 4.7 to 6.03 [74,76].…”
mentioning
confidence: 99%
See 1 more Smart Citation